Anti-ultraviolet high-flame-retardant polyester fiber and preparation method thereof

By introducing core-shell flame-retardant and UV-resistant particles into polyester fibers and utilizing the adaptive regulation of porous alumina-titanium dioxide composites and photothermal carbon dots, the problem of insufficient UV resistance and antioxidant properties of polyester fibers in outdoor environments has been solved, achieving controlled release of active ingredients and performance improvement.

CN121065846APending Publication Date: 2025-12-05JIANGSU HENGKE ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202511359659.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-30
Filing Date
2025-09-23
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing polyester fibers have insufficient UV resistance and antioxidant properties in outdoor environments. The release rate of UV absorbers and antioxidants is uncontrollable and they are prone to aggregation and migration, which affects fiber performance.

Method used

The core-shell flame-retardant and UV-resistant particles are used. Magnesium hydroxide and photothermal carbon dots are loaded onto a porous alumina-titanium dioxide composite carrier and coated with a polyurethane microporous membrane to form core particles, thereby achieving sustained release and adaptive regulation of active ingredients.

Benefits of technology

It significantly improves the UV resistance and flame retardancy of polyester fibers, and the release rate of active ingredients is adaptively adjusted according to the environmental UV intensity, prolonging the UV resistance and antioxidant effect, making it suitable for outdoor applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121065846A_ABST
    Figure CN121065846A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-ultraviolet high-flame-retardant polyester fiber and a preparation method thereof. The polyester fiber is prepared from the following raw materials in parts by weight: 100 parts of polyester chips, 20-60 parts of core-shell flame-retardant anti-ultraviolet particles and 2-4.5 parts of an anti-dripping agent. According to the invention, a porous alumina-titanium dioxide compound is used as a carrier, a magnesium hydroxide flame retardant, iron-doped carbon dots with photo-thermal performance and auxiliaries (an antioxidant and an ultraviolet light absorber) are combined with the carrier to construct a structural system loaded with multiple active components: functionalized flame-retardant particles, and then a polyurethane microporous membrane is coated, so that the flame-retardant polyurethane composite material is obtained. The core-shell type flame-retardant anti-ultraviolet particles are added into polyester fibers, so that the anti-ultraviolet performance and the flame-retardant performance of the polyester fibers can be remarkably improved. The polyester fiber provided by the invention can adaptively increase the release rate of the ultraviolet absorbent and the antioxidant when the ultraviolet property is enhanced in the environment, so that more optimized protection can be provided for a polyester fiber matrix at the moment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of polyester fiber materials, in particular to an ultraviolet-resistant high-flame-retardant polyester fiber and a preparation method thereof. BACKGROUND

[0002] Polyester fiber, commonly known as "polyester", is a synthetic fiber made from organic diacid and diol through chemical polycondensation. It has many advantages, such as high breaking strength and elastic modulus, moderate resilience, excellent heat setting effect, good wear resistance, stable chemical properties, good heat and light resistance, and good corrosion resistance. It is stable to weak acids and weak bases. It has a wide range of applications in home textile manufacturing and industrial textile manufacturing.

[0003] When polyester fiber is applied in outdoor environments, such as tarpaulins, vehicle roofs, ropes, packaging materials (such as non-woven fabrics for cement and sand packaging bags), building non-woven polyester fiber fabrics, and other industrial non-woven fabrics, etc., there are often a large amount of ultraviolet radiation and some oxidative substances in the outdoor environment, which pose a great challenge to the ultraviolet resistance and oxidation resistance of polyester fiber. By adding ultraviolet absorbers and / or inorganic fillers with ultraviolet resistance, adding antioxidants, the ultraviolet resistance and oxidation resistance of polyester fiber can be improved. In traditional solutions, ultraviolet absorbers and antioxidants are usually directly added to the polyester system, such as patent CN111979585A, which discloses a warm and moisture-conducting multifunctional polyester fiber and a preparation method thereof, patent CN105802146A, which discloses a polyester fiber flexible packing belt and a preparation method thereof, patent CN120041963A, which discloses an antibacterial elastic polyester fiber and a preparation method thereof, and patent CN119956520A, which discloses a process for spinning and preparing matt PET fiber chips. The main problems of these patents are: when the amount of addition is small, the time efficiency of providing ultraviolet resistance and anti-aging is short, and when the amount of addition is large, the compatibility problem is easy to occur, which affects the performance of polyester; and the ultraviolet absorbers and antioxidants are directly exposed in the polyester system in large quantities, which will accelerate their failure due to decomposition, surface migration, etc., and shorten the time efficiency of ultraviolet resistance and anti-aging. Building a slow-release system can achieve long-term release of active ingredients and prolong their efficacy, such as patent CN120158132A, which discloses a slow-release type yellowing-resistant additive and its application in coatings, and patent CN120098689A, which discloses a slow-release type antioxidant and its preparation method and application. However, in such solutions, the release rate of active ingredients is not controllable. Taking ultraviolet absorbers as an example, whether the ultraviolet light in the environment becomes stronger or weaker, the release rate of ultraviolet absorbers is not affected, but depends on the slow-release system itself. If the release rate and amount of ultraviolet absorbers can be self-adapted to increase when the ultraviolet light in the environment becomes stronger, it can provide better and more intelligent ultraviolet resistance for the matrix at that time. Obviously, the above solutions cannot achieve this goal.

[0004] Therefore, it is now necessary to improve existing technologies to provide more reliable solutions. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a UV-resistant, high flame-retardant polyester fiber and its preparation method, addressing the shortcomings of the prior art.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: In its first aspect, the present invention provides a UV-resistant, high-flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 20-60 parts core-shell flame-retardant and UV-resistant particles, and 2-4.5 parts anti-drip agent; the core-shell flame-retardant and UV-resistant particles are prepared by the following method:

[0007] S1. Prepare a porous support, which is a composite of porous alumina and titanium dioxide;

[0008] S2. Magnesium hydroxide is loaded onto a porous carrier to obtain flame-retardant particles;

[0009] S3. Modify the flame-retardant particles with a photothermal agent to obtain functionalized flame-retardant particles, wherein the photothermal agent is a carbon dot with photothermal properties.

[0010] S4. Loading additives onto functionalized flame-retardant particles to obtain core particles. The additives include antioxidants and ultraviolet absorbers.

[0011] S5. Coating the core particles with a polyurethane microporous membrane yields core-shell type flame-retardant and UV-resistant particles.

[0012] Preferably, the anti-drip agent is at least one of melamine, benzomelamine, and triallyl isocyanate; the antioxidant is at least one of antioxidant 1010, antioxidant 618, antioxidant 1076, and antioxidant 1098; and the ultraviolet absorber is at least one of UV-P, UV-1, UV-9, UVBP-4, UV-234, and UVP-327.

[0013] Preferably, the core-shell type flame-retardant and UV-resistant particles are prepared by the following method:

[0014] S1. Preparation of porous support: Using tetrabutyl titanate as titanium source, Al(NO3)3·9H2O as aluminum source, hexadecyltrimethylammonium bromide as template agent and ammonium bicarbonate as precipitant, a composite of porous alumina and titanium dioxide, i.e., porous support, is prepared by hydrothermal reaction and calcination.

[0015] S2. The porous support, MgCl2, and NaOH are mixed and reacted to load magnesium hydroxide onto the porous support to obtain flame-retardant particles.

[0016] S3, Magnesium hydroxide loaded: Using glucose, ferric citrate, allyltrimethylammonium chloride, 4-dimethylaminopyridine and indocyanine green as raw materials, and a mixture of ethanol and water as solvent, carbon dots with photothermal properties are synthesized in situ on flame retardant particles by hydrothermal method to obtain functionalized flame retardant particles, which are photothermal agents.

[0017] S4. Loading additives: Additives are loaded onto functionalized flame-retardant particles using a supergravity-assisted impregnation method to obtain core particles. The additives include antioxidants and ultraviolet absorbers.

[0018] S5. Coated with polyurethane microporous membrane: Coating the core particles with a polyurethane microporous membrane yields core-shell type flame-retardant and UV-resistant particles.

[0019] Preferably, step S1 specifically includes:

[0020] Tetrabutyl titanate was added to n-butanol to obtain solution A. Al(NO3)3·9H2O and hexadecyltrimethylammonium bromide were added to deionized water, followed by ammonium bicarbonate. After stirring, solution A was added, and the resulting mixture was added to a reaction vessel. The reaction was carried out at 150-170℃ for 6-24 hours. The solid product was calcined at 400-550℃ for 2-8 hours to obtain a porous support.

[0021] Preferably, step S2 specifically involves: dispersing a porous carrier in deionized water, adding MgCl2, and then adding NaOH aqueous solution dropwise. After the addition is complete, the mixture is stirred and reacted at 40-60℃ for 1-4 hours. The mixture is then filtered, washed, and dried to obtain flame-retardant particles.

[0022] Preferably, step S3 specifically includes:

[0023] S3-1. Disperse flame retardant particles and ferric citrate in deionized water at a temperature of 60-80℃ to obtain mixture 1; add glucose, allyltrimethylammonium chloride, 4-dimethylaminopyridine and indocyanine green to a mixed solvent composed of ethanol and deionized water, and stir to obtain mixture 2.

[0024] S3-2. Add mixture 2 to mixture 1, and transfer the resulting precursor liquid into a reaction vessel. React at 165-190℃ for 4-16 hours, filter, wash, and dry to obtain functionalized flame retardant particles.

[0025] Preferably, step S4 specifically includes:

[0026] S4-1. Add antioxidants and ultraviolet absorbers to acetone to prepare an additive impregnation solution with an antioxidant concentration of 5-20 g / L and an ultraviolet absorber concentration of 3-12 g / L.

[0027] S4-2. Add functionalized flame-retardant particles to the impregnation solution, ultrasonically disperse for 0.5-2 hours, then place in a hypergravity packed bed and treat under hypergravity conditions of 25-100 times the acceleration of gravity for 2-8 hours. Remove the particles, let them stand for 1-4 hours, filter, wash, and dry to obtain the core particles.

[0028] Preferably, step S5 specifically includes:

[0029] S5-1. Add PPG, TDI, and hydroxypropyl silicone oil to acetone, heat to 55-75℃, add triethylenediamine dropwise, stir and react for 1-3 hours, add butanediol and ethylenediamine, stir and react at 70-75℃ for 1.5-6 hours, remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0030] S5-2. Add the modified polyurethane emulsion, core particles, and polyethylene glycol to a mixed solution of butanone and DMF. Stir and react at 65-75℃ for 15-60 min, let stand for 5-30 min, centrifuge, add the obtained solid product to DMF, stir, filter, add the solid product to deionized water at 70-80℃, stir for 2-8 h, filter and dry for h to obtain core-shell flame-retardant and UV-resistant particles.

[0031] Preferably, the core-shell type flame-retardant and UV-resistant particles are prepared by the following method:

[0032] S1. Preparation of porous support:

[0033] Add 0.85-3.4 mL of tetrabutyl titanate to 25-100 mL of n-butanol and stir for 2-10 min to obtain solution A; add 5-20 g of Al(NO3)3·9H2O and 0.12-0.5 g of hexadecyltrimethylammonium bromide to 75-300 mL of deionized water and stir for 5-20 min, then add 4-16 g of ammonium bicarbonate and stir for 15-60 min, then add solution A and sonicate for 0.5-2 h. Add the resulting mixture to a reaction vessel and react at 150-170℃ for 6-24 h. Cool to room temperature, filter, wash, dry, calcine at 650-750℃ for 2-8 h, and grind to obtain a porous support.

[0034] S2. Magnesium hydroxide loaded on a porous support:

[0035] Take 2.5-10g of porous carrier and disperse it in 100-400mL of deionized water, add 1.5-6.3g of MgCl2, and add 30-150mL of 1mol / L NaOH aqueous solution dropwise while stirring. Stir and react at 40-60℃ for 1-4h, filter, wash and dry to obtain flame retardant particles;

[0036] S3. Modify flame-retardant particles with photothermal agents:

[0037] S3-1. Disperse 2.5-10g of flame retardant particles and 612-2450mg of ferric citrate in 50-200mL of deionized water at 60-80℃ to obtain mixture 1; add 450-1800mg of glucose, 200-814mg of allyltrimethylammonium chloride, 122-488mg of 4-dimethylaminopyridine and 220-930mg of indocyanine green to a mixed solvent consisting of 20-80mL of ethanol and 30-120mL of deionized water, stir for 5-30min to obtain mixture 2;

[0038] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 60-80℃ for 5-20 min. Transfer the resulting precursor liquid to the reactor and react at 165-190℃ for 4-16 h. Cool, filter, wash, and dry to obtain functionalized flame retardant particles.

[0039] S4. Loading additives onto functionalized flame-retardant particles:

[0040] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 5-20 g / L and an ultraviolet absorber concentration of 3-12 g / L.

[0041] S4-2. Take 2.5-10g of functionalized flame retardant particles and add them to 50-200mL of impregnation solution. After ultrasonic dispersion for 0.5-2h, place them in a hypergravity packed bed and treat them under hypergravity conditions of 100-400 times the acceleration of gravity for 2-8h. After treatment, remove them, let them stand for 1-4h, filter, wash, and dry them to obtain the core particles.

[0042] S5. Coating the core particles with a polyurethane microporous membrane:

[0043] S5-1. Take 2.5-10g PPG, 1.75-7g TDI, and 0.7-2.8g hydroxypropyl silicone oil and add them to 50-200mL acetone. Under nitrogen protection, heat to 55-75℃, then add 0.005-0.03g triethylenediamine dropwise and stir for 1-3h. Add 1-4mL butanediol and 0.4-1.6mL ethylenediamine, stir and react at 70-75℃ for 1.5-6h, cool to room temperature, and remove acetone by vacuum distillation to obtain the modified polyurethane emulsion.

[0044] S5-2. Take 2.5-10g of modified polyurethane emulsion, 1.25-5g of core particles, and 0.28-1.12g of polyethylene glycol and add them to a mixed solution consisting of 15-60mL of butanone and 15-60mL of DMF. Stir for 5-30min, react at 65-75℃ for 15-60min, let stand for 5-30min, cool to room temperature, and centrifuge. Add the obtained solid product to 25-100mL of DMF, stir for 5-20min, filter, add the solid product to 50-200mL of deionized water at 70-80℃, stir for 2-8h, filter and dry to obtain core-shell flame-retardant and UV-resistant particles.

[0045] Preferably, the core-shell type flame-retardant and UV-resistant particles are prepared by the following method:

[0046] S1. Preparation of porous support:

[0047] 1.7 mL of tetrabutyl titanate was added to 50 mL of n-butanol and stirred for 5 min to obtain solution A. 10 g of Al(NO3)3·9H2O and 0.25 g of hexadecyltrimethylammonium bromide were added to 150 mL of deionized water and stirred for 10 min. Then, 7.9 g of ammonium bicarbonate was added and stirred for 30 min. Solution A was then added and ultrasonically dispersed for 1 h. The resulting mixture was added to a reaction vessel and reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was filtered, washed, dried, calcined at 700 °C for 4 h, and ground to obtain a porous support.

[0048] S2. Magnesium hydroxide loaded on a porous support:

[0049] Take 5g of porous carrier and add it to 200mL of deionized water. Disperse it by sonication for 30min. Then add 3.15g of MgCl2 and stir for 15min. Add 75mL of 1mol / L NaOH aqueous solution dropwise while stirring. After the addition is complete, stir and react at 50℃ for 2h. Filter, wash and dry to obtain flame retardant particles.

[0050] S3. Modify flame-retardant particles with photothermal agents:

[0051] S3-1. Add 5g of flame retardant particles and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0052] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain precursor liquid. Transfer the precursor liquid to a polytetrafluoroethylene-lined reactor, react at 175°C for 8 h, cool, filter, wash, and dry to obtain functionalized flame retardant particles.

[0053] S4. Loading additives onto functionalized flame-retardant particles:

[0054] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0055] S4-2. Take 5g of functionalized flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a hypergravity packed bed and treat them under hypergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the hypergravity packed bed, let them stand for 2h, filter, wash, and dry them to obtain the core particles.

[0056] S5. Coating the core particles with a polyurethane microporous membrane:

[0057] S5-1. Take 5g PPG, 3.5g TDI, and 1.4g hydroxypropyl silicone oil and add them to 100mL acetone. Under nitrogen protection, heat to 65℃, then add 0.015g triethylenediamine dropwise and stir for 1.5h. Add 2mL butanediol and 0.8mL ethylenediamine, stir for 3h at 72℃, cool to room temperature, and remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0058] S5-2. Take 5g of modified polyurethane emulsion, 2.5g of core particles, and 0.56g of polyethylene glycol and add them to a mixed solution of 30mL of butanone and 30mL of DMF. Stir for 15min, react at 70℃ for 30min, let stand for 15min, cool to room temperature and centrifuge. Add the obtained solid product to 50mL of DMF, stir for 10min, filter, add the solid product to 100mL of deionized water at 75℃, stir for 4h, filter, and vacuum dry the solid product at 50℃ for 12h to obtain core-shell flame-retardant and UV-resistant particles.

[0059] The present invention also provides a method for preparing the UV-resistant and highly flame-retardant polyester fiber as described above, comprising the following steps:

[0060] 1) Dry the polyester chips under vacuum at 100-120℃ for 6-24 hours, and then mix them with core-shell flame retardant and UV-resistant particles and anti-drip agent to obtain polyester mixture;

[0061] 2) The polyester blend is melt-extruded at 230-245℃, and the resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 250-270℃ and the spinning speed is 600-900m / min.

[0062] Invention Mechanism:

[0063] I. Preparation Mechanism

[0064] (1) First, using Al(NO3)3·9H2O as the aluminum source, hexadecyltrimethylammonium bromide as the template agent and ammonium bicarbonate as the precipitant, a porous alumina was prepared by a traditional hydrothermal reaction combined with calcination. The special feature is that in this invention, tetrabutyl titanate is used as the titanium source, and titanium dioxide is doped into the porous alumina to obtain a porous alumina-titanium dioxide composite, i.e., a porous carrier, denoted as TiO2-Al2O3.

[0065] TiO2-Al2O3 serves as a carrier for loading various active components (magnesium hydroxide, carbon dots, and additives), and its porous structure provides a slow-release function for the additives. Furthermore, the addition of alumina to polyester fibers enhances their abrasion resistance, strength, and thermal stability, and helps improve their flame retardancy. The doped titanium dioxide exhibits excellent ultraviolet light absorption and can improve the fiber's strength, weather resistance, and heat resistance.

[0066] (2) Then, taking advantage of the well-developed pore structure and large specific surface area of ​​the porous carrier, magnesium hydroxide is loaded onto it as a flame retardant to obtain flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2. Magnesium hydroxide, as a commonly used inorganic flame retardant, releases water molecules and absorbs a large amount of heat when it decomposes upon heating, thereby reducing the temperature of the polyester fiber and delaying or preventing the combustion process, which can significantly improve the flame retardant performance of the polyester fiber.

[0067] (3) Then, using glucose, allyltrimethylammonium chloride, 4-dimethylaminopyridine and indocyanine green as composite carbon sources and iron citrate as dopant, iron-doped carbon dots with photothermal properties were synthesized in situ on the flame retardant particles by a one-pot hydrothermal method. These carbon dots are photothermal agents, and functionalized flame retardant particles are obtained, denoted as TiO2-Al2O3@Mg(OH)2@Fe-CDs. During the preparation process, on the one hand, the adsorption effect of the rich pore structure of TiO2-Al2O3@Mg(OH)2 allows components such as the composite carbon source to be adsorbed onto the surface of TiO2-Al2O3@Mg(OH)2 or enter its pores. On the other hand, iron citrate is first mixed with TiO2-Al2O3@Mg(OH)2, and iron ions combine with the hydroxyl groups on the surface of TiO2-Al2O3@Mg(OH)2 through coordination and other interactions. Subsequently, iron ions can also combine with the components in the composite carbon source through coordination with functional groups such as carboxyl and amino groups. This allows each component to be adsorbed in large quantities by TiO2-Al2O3@Mg(OH)2, creating favorable conditions for the in-situ deposition of carbon dots on TiO2-Al2O3@Mg(OH)2.

[0068] The iron-doped carbon dots synthesized in situ in this invention have excellent ultraviolet absorption properties, which can significantly improve the UV resistance of polyester fibers. At the same time, they also exhibit good photothermal properties (the ability to convert light energy into heat energy). While absorbing ultraviolet rays, they can achieve a local heating effect and can serve as a high-performance photothermal agent. In the core-shell flame-retardant and UV-resistant particle structure system constructed in this invention, they can play a role in "adaptive and intelligent adjustment" of the micropores of polyurethane microporous membranes according to the UV content of the environment.

[0069] Allyltrimethylammonium chloride (QAC) has been reported as a carbon source for preparing carbon dots with photothermal properties. Lü Ju et al. used QAC with Cu... 2+ A Cu-doped carbon dot with photothermal properties was prepared by hydrothermal reaction, and its red light photothermal performance was verified. It can be used as a photothermal agent in photothermal therapy (Preparation, characterization and performance of photothermal and photodynamic synergistic antibacterial carbon dots [J]. Fine Chemicals, 2024, 41(8):1745-1753.). However, after testing, its photothermal efficiency was only 21.7% (808 nm laser irradiation), and it is necessary to further improve its photothermal efficiency. In order to prepare carbon dots with ultraviolet photothermal properties, a series of improvements were made on the basis of the present invention. Glucose, 4-dimethylaminopyridine and indocyanine green were added as composite carbon sources, and Fe with variable valence state was used. 3+ Replace Cu 2+ After doping, the resulting carbon dots exhibited excellent ultraviolet absorption and ultraviolet photothermal performance, with a photothermal efficiency of up to 45.2%.

[0070] Among them, Fe 3+ Doping can alter the electron cloud distribution and increase the electron cloud density of carbon dots, forming new impurity energy levels and narrowing the band gap of the material, thereby expanding the light absorption range. Furthermore, by anchoring the carbon dot framework with iron, it exposes more active sites, enhancing the capture efficiency of incident photons and ultimately improving light absorption efficiency and energy utilization, as well as enhancing ultraviolet absorption performance and photothermal efficiency. Adding 4-dimethylaminopyridine enriches the strong electron-donating groups in carbon dots, improving the absorption coefficient and photothermal performance, which is consistent with the report in the literature "Dongmei Xi, Ming Xiao, Jianfang Cao, Luyang Zhao, Ning Xu, Saran Long, Jiangli Fan, Kun Shao, Wen Sun*, Xuehai Yan, and Xiaojun Peng*. NIR Light-Driving Barrier-Free Group Rotation in Nanoparticles with an 88.3% Photothermal Conversion Efficiency for Photothermal Therapy. Adv. Mater. 2020, 32, 190785". Indocyanine green (ICG) is a near-infrared fluorescent dye with high absorption rate.

[0071] (4) Then, using the rich pore structure of the functional flame retardant particles, antioxidants and ultraviolet absorbers are loaded onto the functional flame retardant particles by supergravity-assisted impregnation to obtain core particles. Since supergravity-assisted impregnation is used, the efficiency and loading of impregnation can be improved. The antioxidants and ultraviolet absorbers are loaded in the pores, which can achieve a better slow-release effect. Thus, the antioxidants and ultraviolet absorbers can be released slowly and for a long time in the polyester fiber matrix, providing a more lasting effect. This can effectively avoid the premature failure of antioxidants and ultraviolet absorbers caused by aggregation and surface migration in the polyester system, and reduce their adverse effects on the polyester fiber matrix.

[0072] (5) Finally, a polyurethane microporous membrane is coated on the core particles to obtain core-shell flame-retardant and UV-resistant particles. In this process, hydroxypropyl silicone oil is added to the conventional polyurethane preparation raw materials PPG and TDI, and triethylenediamine is used as a catalyst to prepare a modified polyurethane emulsion. Then, the core particles are mixed with the modified polyurethane emulsion using the traditional solvent-non-solvent method (Wang Quanjie, Zhang Yuzhou, Yang Yang, et al. Effect of different porogens on the permeability of polyurethane microporous membranes [J]. Leather Science and Engineering, 2011(3):6.DOI:10.3969 / j.issn.1004-7964.2011.03.005.), with polyethylene glycol as the porogen, DMF as the solvent and water as the non-solvent, and a polyurethane microporous membrane is coated on the core particles.

[0073] Firstly, one drawback of using inorganic reinforcing particles TiO2, Al2O3, and Mg(OH)2 in polyester fiber systems is their poor compatibility with the system and difficulty in uniform dispersion. Furthermore, TiO2, as an anti-UV active component, and Mg(OH)2, as a flame-retardant active component, are prone to aggregation and surface migration in polyester systems, leading to premature deactivation of the components and deterioration of the substrate performance. Coating with polyurethane microporous membranes can significantly improve the compatibility between the core particles and the polyester fiber system. Combined with the multi-component organically bonded structure on the core particles, this can simultaneously solve the problem of the difficulty in uniformly dispersing inorganic components TiO2, Al2O3, Mg(OH)2, and Fe-CDs in polyester fiber systems. Furthermore, the polyurethane microporous membrane coating avoids direct contact between TiO2, Mg(OH)2, and polyester, reducing their negative impact on the polyester system's performance and mitigating phenomena such as aggregation and surface migration. The polyurethane microporous membrane also provides a certain degree of shielding for TiO2, preventing premature consumption of its UV absorption activity and providing a degree of sustained-release effect, thus prolonging its effectiveness. In the event of a fire, the high temperature causes the polyurethane microporous membrane to rapidly expand and melt, fully exposing Mg(OH)2 without affecting the timely application of its flame-retardant effect.

[0074] Secondly, polyurethane also has good elasticity and abrasion resistance. Adding it to polyester fibers can improve the elasticity and comfort of polyester fibers and enhance the durability of the fabric. The addition of hydroxypropyl silicone oil can improve water repellency (Chen Zufeng, Lin Weihong. Synthesis and application of comb-type waterborne polyurethane coated organosilicon fluorine-free high-efficiency water repellent [J]. Guangzhou Chemical Industry, 2023, 51(11):71-74.), and improve the waterproof ability of polyester fibers.

[0075] Thirdly, unlike conventional polymer coating modification methods, this invention coats the core particles with a porous polyurethane film. This film structure, combined with the iron-doped carbon dots possessing photothermal properties, enables "adaptive regulation" of UV resistance and antioxidant properties. The regulation results in the following: the stronger the ultraviolet radiation, the greater the amount of antioxidants and UV absorbers released from the core-shell flame-retardant and UV-resistant particles, and the more UV-resistant carbon dots and porous carriers are exposed, thus adaptively enhancing the provided UV resistance and antioxidant properties. This is further explained below:

[0076] When polyester fibers are irradiated with ultraviolet light, the photothermal agent (Fe-CDs) absorbs the ultraviolet light, providing UV protection while simultaneously raising the local temperature. The thermal expansion and contraction cause the micropores of the polyurethane microporous membrane to expand, increasing the membrane's permeability. At the same time, the increased temperature accelerates molecular motion, prompting the release of antioxidants and UV absorbers loaded in the porous carrier. The combination of these two effects allows more antioxidants and UV absorbers to be released from the core-shell flame-retardant and UV-resistant particles into the polyester fiber system. The increased UV absorber enhances UV absorption performance, thus matching the increased UV intensity. Simultaneously, the increased membrane permeability increases the exposure of TiO2 and Fe-CDs in the core particles. Increased TiO2 exposure enhances the UV absorption capacity provided by TiO2. However, while absorbing ultraviolet light, TiO2 easily generates strong oxidizing substances, such as hydroxyl radicals (·OH), which can damage the polyester structure. The increased release of antioxidants can promptly capture these strong oxidizing substances, thus avoiding the negative effects of TiO2's UV protection function. Increased exposure to Fe-CDs leads to the absorption of more ultraviolet radiation and the generation of more heat, which in turn causes the micropores of the polyurethane microporous membrane to expand further, thereby producing a boost in UV protection. Ultimately, this achieves "intelligent adaptive regulation" of UV protection and antioxidant properties. This regulation can adapt the protective performance provided by the active components in the system according to changes in the environment, thus prolonging the efficacy of the active components and fully leveraging their effects.

[0077] It is important to understand that the upper limit of the localized temperature rise caused by the core-shell flame-retardant and UV-resistant particles in this invention is far from reaching the level that would cause combustion. When added to polyester fibers, according to the dosage range of this invention, under normal outdoor application scenarios, the upper limit of the temperature does not exceed 100°C (in the photothermal performance experiment, when the dosage of core-shell flame-retardant and UV-resistant particles was at its maximum, the highest localized temperature in the polyester fiber was approximately 97°C). This is mainly due to limitations imposed by the light source power (in normal outdoor application scenarios, UV light sources mainly come from sunlight, and their intensity is within a normal range), the balance between heat generation and dissipation, and the photothermal efficiency of the functionalized flame-retardant particles. Therefore, it will not pose a fire hazard due to temperature rise. However, it should also be noted that due to this photothermal property, the polyester fibers prepared in this invention are not suitable for use in close-fitting fabric products to avoid burns to the human body; however, they are very suitable for many non-wearable products used in outdoor environments. Outdoor environments often inevitably involve large amounts of ultraviolet radiation and the attack of some oxidizing substances, posing a significant challenge to the UV resistance and oxidation resistance of polyester fibers. The polyester fiber of this invention has "adaptive regulation" of UV protection and antioxidant properties, which can prolong the UV protection and antioxidant effects. Therefore, it will be very suitable for these scenarios, such as tarpaulins, vehicle roofs, ropes, packaging materials (such as non-woven fabrics for cement and sand packaging bags), non-woven polyester fiber cloth for construction, and other industrial non-woven fabrics, etc.

[0078] The beneficial effects of this invention are:

[0079] This invention uses a porous alumina-titanium dioxide composite as a carrier to combine magnesium hydroxide flame retardant, iron-doped carbon dots with photothermal properties, and additives (antioxidants and UV absorbers) to form a multi-active component-loaded structural system: functionalized flame-retardant particles. These particles are then coated with a polyurethane microporous membrane to obtain a core-shell type flame-retardant and UV-resistant particle. Adding this particle to polyester fibers significantly improves their UV resistance and flame-retardant properties. The polyester fibers provided by this invention can adaptively increase the release rate of UV absorbers and antioxidants when UV radiation in the environment increases, thus providing optimized protection for the polyester fiber matrix.

[0080] This invention achieves "adaptive regulation" of UV resistance and antioxidant properties by coating a porous polyurethane film onto core particles loaded with active components such as antioxidants and UV absorbers. This, combined with iron-doped carbon dots possessing photothermal properties, results in a greater amount of antioxidants and UV absorbers released from the core-shell flame-retardant UV-resistant particles, and more UV-resistant carbon dots and porous carriers are exposed. This adaptively enhances the UV resistance and antioxidant properties, perfectly adapting to the external environment. This allows for better utilization of the active components like antioxidants and UV absorbers, prolonging their effectiveness and improving the UV resistance and duration of the polyester fiber. This "adaptive regulation" makes the polyester fiber prepared by this invention highly effective and has great application potential in non-wearable fabric products for outdoor applications, such as tarpaulins, automotive roofs, ropes, packaging materials (e.g., non-woven fabrics for cement and gravel packaging bags), architectural non-woven polyester fiber fabrics, and other industrial non-woven fabrics. Attached Figure Description

[0081] Figure 1 The infrared absorption spectra of the porous support (TiO2-Al2O3) and functionalized flame-retardant particles [TiO2-Al2O3@Mg(OH)2@Fe-CDs] prepared in Example 1 are shown.

[0082] Figure 2 The temperature-time curves are for the flame-retardant particles [TiO2-Al2O3@Mg(OH)2] and functionalized flame-retardant particles [TiO2-Al2O3@Mg(OH)2@Fe-CDs] prepared in Example 1.

[0083] Figure 3 The results are the photothermal conversion efficiency test results of the core-shell flame-retardant and UV-resistant particles in Examples 1-4 and Comparative Examples 2-3;

[0084] Figure 4 The UV-Vis absorption spectra of the core-shell flame-retardant and UV-resistant particles prepared in Example 1, Comparative Example 1, and Comparative Example 4 are shown.

[0085] Figure 5 The results of the UV absorber release performance test of the core-shell flame-retardant and UV-resistant particles prepared in Example 1;

[0086] Figure 6 The UVA resistance test results are for the polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6.

[0087] Figure 7 The UVB resistance test results are for the polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6.

[0088] Figure 8 The flame retardant performance test results are for the polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6.

[0089] Figure 9 The tensile strength test results are for the polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6;

[0090] Figure 10 The results are the test results of the breaking strength retention rate of the polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6 after aging. Detailed Implementation

[0091] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.

[0092] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0093] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available. For examples where specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer are followed. For reagents or instruments whose manufacturers are not specified, they are all commercially available products.

[0094] The main sources of raw materials in the following examples and comparative examples are explained below:

[0095] Polyester chips, model CB-602, relative viscosity 0.8 dl / g, acid value 35 mg KOH / g, Far Eastern Textiles (Shanghai) Co., Ltd.

[0096] Triallyl isocyanurate, Jiangsu Minglin Chemical Technology Co., Ltd.;

[0097] Tetrabutyl titanate, hexadecyltrimethylammonium bromide, Jiangsu Minglin Chemical Technology Co., Ltd.;

[0098] Allyltrimethylammonium chloride, Jiangsu Runfeng Synthetic Technology Co., Ltd.;

[0099] 4-Dimethylaminopyridine, Nanjing Chemical Reagent Co., Ltd.;

[0100] Indocyanine green, brand: Kramar, Shanghai Ziyi Reagent Factory;

[0101] Antioxidant 1010, UV absorber UV-9, Nanjing Milan Chemical Co., Ltd.;

[0102] Hydroxypropyl silicone oil, double-terminated hydroxypropyl silicone oil, molecular weight 2000, hydroxyl content 1.7%, Hubei Darli Chemical Co., Ltd.

[0103] PPG (polypropylene glycol), polypropylene glycol 2000, Shanghai Hongzhuang Chemical Technology Co., Ltd.;

[0104] Polyethylene glycol, PEG-1000, Haian Petrochemical Plant, Jiangsu Province;

[0105] Toluene diisocyanate (TDI), triethylenediamine, Nantong Runfeng Petrochemical Co., Ltd.;

[0106] Magnesium hydroxide, with an average particle size of 5 μm, is produced by Nantong Runfeng Petrochemical Co., Ltd.

[0107] Example 1

[0108] A UV-resistant and highly flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 42 parts core-shell flame-retardant and UV-resistant particles, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate.

[0109] The method for preparing this polyester fiber includes the following steps:

[0110] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with core-shell flame retardant and UV-resistant particles and anti-drip agent at 500 rpm for 30 minutes to obtain polyester mixture.

[0111] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 240°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 750 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0112] The core-shell type flame-retardant and UV-resistant particles were prepared by the following method:

[0113] S1. Preparation of porous support:

[0114] 1.7 mL of tetrabutyl titanate was added to 50 mL of n-butanol and stirred for 5 min to obtain solution A. 10 g of Al(NO3)3·9H2O and 0.25 g of hexadecyltrimethylammonium bromide were added to 150 mL of deionized water and stirred for 10 min. Then, 7.9 g of ammonium bicarbonate was added and stirred for 30 min. Solution A was then added and ultrasonically dispersed for 1 h. The resulting mixture was added to a reaction vessel and reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was filtered, washed, vacuum dried at 90 °C for 6 h, calcined at 700 °C for 4 h, and ground to obtain a porous support, denoted as TiO2-Al2O3.

[0115] S2. Magnesium hydroxide loaded on a porous support:

[0116] Take 5g of porous carrier and add it to 200mL of deionized water. Disperse it by sonication for 30min. Then add 3.15g of MgCl2 and stir for 15min. Add 75mL of 1mol / L NaOH aqueous solution dropwise while stirring. After the addition is complete, stir and react at 50℃ for 2h. Filter, wash with deionized water, and vacuum dry at 80℃ for 4h to obtain flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2.

[0117] S3. Modify flame-retardant particles with photothermal agents:

[0118] S3-1. Add 5g of flame retardant particles and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0119] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain a precursor solution. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175°C for 8 h, cool to room temperature, filter, wash the solid product with ethanol, and vacuum dry at 90°C for 12 h to obtain functionalized flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2@Fe-CDs.

[0120] S4. Loading additives onto functionalized flame-retardant particles:

[0121] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0122] Among them, the antioxidant is antioxidant 1010, and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0123] S4-2. Take 5g of functionalized flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0124] S5. Coating the core particles with a polyurethane microporous membrane:

[0125] S5-1. Take 5g PPG (polypropylene glycol), 3.5g TDI (toluene diisocyanate), and 1.4g hydroxypropyl silicone oil and add them to 100mL acetone. Under nitrogen protection, heat to 65℃, then add 0.015g triethylenediamine dropwise and stir for 1.5h. Add 2mL butanediol and 0.8mL ethylenediamine, stir for 3h at 72℃, cool to room temperature, and remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0126] S5-2. Take 5g of modified polyurethane emulsion, 2.5g of core particles, and 0.56g of polyethylene glycol and add them to a mixed solution of 30mL of butanone and 30mL of DMF (N,N-dimethylformamide). Stir for 15min, react at 70℃ for 30min, let stand for 15min, cool to room temperature and centrifuge. Add the obtained solid product to 50mL of DMF, stir for 10min, filter, add the solid product to 100mL of deionized water at 75℃, stir for 4h, filter, and vacuum dry the solid product at 50℃ for 12h to obtain core-shell flame-retardant and UV-resistant particles.

[0127] Example 2

[0128] A UV-resistant and highly flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 42 parts core-shell flame-retardant and UV-resistant particles, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate.

[0129] The method for preparing this polyester fiber includes the following steps:

[0130] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with core-shell flame retardant and UV-resistant particles and anti-drip agent at 500 rpm for 30 minutes to obtain polyester mixture.

[0131] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 240°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 750 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0132] The core-shell type flame-retardant and UV-resistant particles were prepared by the following method:

[0133] S1. Preparation of porous support:

[0134] 1.7 mL of tetrabutyl titanate was added to 50 mL of n-butanol and stirred for 5 min to obtain solution A. 10 g of Al(NO3)3·9H2O and 0.25 g of hexadecyltrimethylammonium bromide were added to 150 mL of deionized water and stirred for 10 min. Then, 7.9 g of ammonium bicarbonate was added and stirred for 30 min. Solution A was then added and ultrasonically dispersed for 1 h. The resulting mixture was added to a reaction vessel and reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was filtered, washed, vacuum dried at 90 °C for 6 h, calcined at 700 °C for 4 h, and ground to obtain a porous support, denoted as TiO2-Al2O3.

[0135] S2. Magnesium hydroxide loaded on a porous support:

[0136] Take 5g of porous carrier and add it to 200mL of deionized water. Disperse it by sonication for 30min. Then add 3.15g of MgCl2 and stir for 15min. Add 75mL of 1mol / L NaOH aqueous solution dropwise while stirring. After the addition is complete, stir and react at 50℃ for 2h. Filter, wash with deionized water, and vacuum dry at 80℃ for 4h to obtain flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2.

[0137] S3. Modify flame-retardant particles with photothermal agents:

[0138] S3-1. Add 5g of flame retardant particles and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0139] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain a precursor solution. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175°C for 8 h, cool to room temperature, filter, wash the solid product with ethanol, and vacuum dry at 90°C for 12 h to obtain functionalized flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2@Fe-CDs.

[0140] S4. Loading additives onto functionalized flame-retardant particles:

[0141] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0142] Among them, the antioxidant is antioxidant 1010, and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0143] S4-2. Take 5g of functionalized flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0144] S5. Coating the core particles with a polyurethane microporous membrane:

[0145] S5-1. Take 5g PPG (polypropylene glycol), 3.5g TDI (toluene diisocyanate), and 1.4g hydroxypropyl silicone oil and add them to 100mL acetone. Under nitrogen protection, heat to 65℃, then add 0.015g triethylenediamine dropwise and stir for 1.5h. Add 2mL butanediol and 0.8mL ethylenediamine, stir for 3h at 72℃, cool to room temperature, and remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0146] S5-2. Take 5g of modified polyurethane emulsion, 2.5g of core particles, and 0.85g of polyethylene glycol and add them to a mixed solution of 30mL of butanone and 30mL of DMF (N,N-dimethylformamide). Stir for 15min, react at 70℃ for 30min, let stand for 15min, cool to room temperature and centrifuge. Add the obtained solid product to 50mL of DMF, stir for 10min, filter, add the solid product to 100mL of deionized water at 75℃, stir for 4h, filter, and vacuum dry the solid product at 50℃ for 12h to obtain core-shell flame-retardant and UV-resistant particles.

[0147] Example 3

[0148] A UV-resistant and highly flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 42 parts core-shell flame-retardant and UV-resistant particles, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate.

[0149] The method for preparing this polyester fiber includes the following steps:

[0150] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with core-shell flame retardant and UV-resistant particles and anti-drip agent at 500 rpm for 30 minutes to obtain polyester mixture.

[0151] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 240°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 750 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0152] The core-shell type flame-retardant and UV-resistant particles were prepared by the following method:

[0153] S1. Preparation of porous support:

[0154] 1.7 mL of tetrabutyl titanate was added to 50 mL of n-butanol and stirred for 5 min to obtain solution A. 10 g of Al(NO3)3·9H2O and 0.25 g of hexadecyltrimethylammonium bromide were added to 150 mL of deionized water and stirred for 10 min. Then, 7.9 g of ammonium bicarbonate was added and stirred for 30 min. Solution A was then added and ultrasonically dispersed for 1 h. The resulting mixture was added to a reaction vessel and reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was filtered, washed, vacuum dried at 90 °C for 6 h, calcined at 700 °C for 4 h, and ground to obtain a porous support, denoted as TiO2-Al2O3.

[0155] S2. Magnesium hydroxide loaded on a porous support:

[0156] Take 5g of porous carrier and add it to 200mL of deionized water. Disperse it by sonication for 30min. Then add 3.15g of MgCl2 and stir for 15min. Add 75mL of 1mol / L NaOH aqueous solution dropwise while stirring. After the addition is complete, stir and react at 50℃ for 2h. Filter, wash with deionized water, and vacuum dry at 80℃ for 4h to obtain flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2.

[0157] S3. Modify flame-retardant particles with photothermal agents:

[0158] S3-1. Add 5g of flame retardant particles and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0159] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain a precursor solution. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175°C for 8 h, cool to room temperature, filter, wash the solid product with ethanol, and vacuum dry at 90°C for 12 h to obtain functionalized flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2@Fe-CDs.

[0160] S4. Loading additives onto functionalized flame-retardant particles:

[0161] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0162] Among them, the antioxidant is antioxidant 1010, and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0163] S4-2. Take 5g of functionalized flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0164] S5. Coating the core particles with a polyurethane microporous membrane:

[0165] S5-1. Take 5g PPG (polypropylene glycol), 3.5g TDI (toluene diisocyanate), and 1.4g hydroxypropyl silicone oil and add them to 100mL acetone. Under nitrogen protection, heat to 65℃, then add 0.015g triethylenediamine dropwise and stir for 1.5h. Add 2mL butanediol and 0.8mL ethylenediamine, stir for 3h at 72℃, cool to room temperature, and remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0166] S5-2. Take 5g of modified polyurethane emulsion, 2.5g of core particles, and 1.0g of polyethylene glycol and add them to a mixed solution of 30mL of butanone and 30mL of DMF (N,N-dimethylformamide). Stir for 15min, react at 70℃ for 30min, let stand for 15min, cool to room temperature and centrifuge. Add the obtained solid product to 50mL of DMF, stir for 10min, filter, add the solid product to 100mL of deionized water at 75℃, stir for 4h, filter, and vacuum dry the solid product at 50℃ for 12h to obtain core-shell flame-retardant and UV-resistant particles.

[0167] Example 4

[0168] A UV-resistant and highly flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 42 parts core-shell flame-retardant and UV-resistant particles, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate.

[0169] The method for preparing this polyester fiber includes the following steps:

[0170] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with core-shell flame retardant and UV-resistant particles and anti-drip agent at 600 rpm for 25 minutes to obtain polyester mixture.

[0171] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 245°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 700 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0172] The core-shell type flame-retardant and UV-resistant particles were prepared by the following method:

[0173] S1. Preparation of porous support:

[0174] 1.7 mL of tetrabutyl titanate was added to 50 mL of n-butanol and stirred for 5 min to obtain solution A. 10 g of Al(NO3)3·9H2O and 0.25 g of hexadecyltrimethylammonium bromide were added to 150 mL of deionized water and stirred for 10 min. Then, 7.9 g of ammonium bicarbonate was added and stirred for 30 min. Solution A was then added and ultrasonically dispersed for 1 h. The resulting mixture was added to a reaction vessel and reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was filtered, washed, vacuum dried at 90 °C for 6 h, calcined at 700 °C for 4 h, and ground to obtain a porous support, denoted as TiO2-Al2O3.

[0175] S2. Magnesium hydroxide loaded on a porous support:

[0176] Take 5g of porous carrier and add it to 200mL of deionized water. Disperse it by sonication for 30min. Then add 3.15g of MgCl2 and stir for 15min. Add 75mL of 1mol / L NaOH aqueous solution dropwise while stirring. After the addition is complete, stir and react at 50℃ for 2h. Filter, wash with deionized water, and vacuum dry at 80℃ for 4h to obtain flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2.

[0177] S3. Modify flame-retardant particles with photothermal agents:

[0178] S3-1. Add 5g of flame retardant particles and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0179] S3-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain a precursor solution. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175°C for 8 h, cool to room temperature, filter, wash the solid product with ethanol, and vacuum dry at 90°C for 12 h to obtain functionalized flame retardant particles, denoted as TiO2-Al2O3@Mg(OH)2@Fe-CDs.

[0180] S4. Loading additives onto functionalized flame-retardant particles:

[0181] S4-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0182] Among them, the antioxidant is antioxidant 1010, and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0183] S4-2. Take 5g of functionalized flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 100 times the acceleration of gravity for 5h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0184] S5. Coating the core particles with a polyurethane microporous membrane:

[0185] S5-1. Take 5g PPG (polypropylene glycol), 3.5g TDI (toluene diisocyanate), and 1.4g hydroxypropyl silicone oil and add them to 100mL acetone. Under nitrogen protection, heat to 68℃, then add 0.015g triethylenediamine dropwise and stir for 1.5h. Add 2mL butanediol and 0.8mL ethylenediamine, stir for 3h at 75℃, cool to room temperature, and remove acetone by vacuum distillation to obtain modified polyurethane emulsion.

[0186] S5-2. Take 5g of modified polyurethane emulsion, 2.5g of core particles, and 0.56g of polyethylene glycol and add them to a mixed solution of 30mL of butanone and 30mL of DMF (N,N-dimethylformamide). Stir for 15min, react at 72℃ for 30min, let stand for 15min, cool to room temperature and centrifuge. Add the obtained solid product to 50mL of DMF, stir for 10min, filter, add the solid product to 100mL of deionized water at 75℃, stir for 4h, filter, and vacuum dry the solid product at 50℃ for 12h to obtain core-shell flame-retardant and UV-resistant particles.

[0187] Comparative Example 1

[0188] The only difference between this comparative example and Example 1 is that:

[0189] Core-shell flame-retardant and UV-resistant particles are prepared by the following method:

[0190] S1. Prepare a porous support, following the same steps as in Example 1;

[0191] S2. Magnesium hydroxide is loaded onto a porous support to prepare flame-retardant particles, the steps of which are the same as in Example 1.

[0192] S3. Loading additives onto flame-retardant particles:

[0193] S3-1. Add antioxidants and ultraviolet absorbers to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L.

[0194] Among them, the antioxidant is antioxidant 1010, and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0195] S3-2. Take 5g of flame retardant particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0196] S4. Coat the core particles with a polyurethane microporous membrane, following the same steps as in Example 1.

[0197] Comparative Example 2

[0198] The only difference between this comparative example and Example 1 is that ferric citrate is not added in step S3-1.

[0199] Comparative Example 3

[0200] The only difference between this comparative example and Example 1 is that indocyanine green is not added in step S3-1.

[0201] Comparative Example 4

[0202] The only difference between this comparative example and Example 1 is that:

[0203] Step S1 in preparing core-shell flame-retardant and UV-resistant particles is as follows:

[0204] Take 10g of Al(NO3)3·9H2O and 0.25g of hexadecyltrimethylammonium bromide and add them to 150mL of deionized water. After stirring for 10min, add 7.9g of ammonium bicarbonate and stir for 30min. Then add 50mL of n-butanol and sonicate for 1h. Add the resulting mixture to a reaction vessel and react at 160℃ for 12h. Cool to room temperature, filter, wash, vacuum dry at 90℃ for 6h, calcine at 700℃ for 4h, and grind to obtain a porous support.

[0205] Comparative Example 5

[0206] A UV-resistant, highly flame-retardant polyester fiber, the raw materials for which are prepared include the following components by weight: 100 parts polyester chips, 39 parts core-shell UV-resistant particles, 3 parts magnesium hydroxide, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate; the preparation method of this polyester fiber includes the following steps:

[0207] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with core-shell UV-resistant particles, magnesium hydroxide, and anti-drip agent at 600 rpm for 25 minutes to obtain the polyester mixture.

[0208] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 245°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 700 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0209] The core-shell type UV-resistant particles were prepared by the following method:

[0210] S1. Prepare a porous support, following the same steps as in Example 1;

[0211] S2. Modification of photothermal agent on porous support:

[0212] S2-1. Add 5g of porous carrier and 1225mg of ferric citrate to 100mL of deionized water at 70℃ and sonicate for 30min to obtain mixture 1; add 900mg of glucose, 407mg of allyltrimethylammonium chloride, 244mg of 4-dimethylaminopyridine and 465mg of indocyanine green to a mixed solvent consisting of 40mL of ethanol and 60mL of deionized water and stir for 15min to obtain mixture 2.

[0213] S2-2. Add mixture 2 to mixture 1 under stirring, and ultrasonically disperse at 70°C for 10 min to obtain precursor liquid. Transfer the precursor liquid to a reaction vessel lined with polytetrafluoroethylene, react at 175°C for 8 h, cool to room temperature, filter, wash the solid product with ethanol, and vacuum dry at 90°C for 12 h to obtain functionalized particles.

[0214] S3. Loading additives onto functionalized particles:

[0215] S3-1. Add antioxidant and ultraviolet absorber to acetone, stir evenly, and prepare an auxiliary impregnation solution with an antioxidant concentration of 10 g / L and an ultraviolet absorber concentration of 6 g / L; wherein, the antioxidant is antioxidant 1010 and the ultraviolet absorber is ultraviolet absorber UV-9 (2-hydroxy-4-methoxybenzophenone).

[0216] S3-2. Take 5g of functionalized particles and add them to 100mL of impregnation solution. After ultrasonic dispersion for 1h, place them in a supergravity packed bed (i.e., a rotating packed bed) and treat them under supergravity conditions of 150 times the acceleration of gravity for 4h. Then, remove them from the supergravity packed bed, let them stand for 2h, filter them, wash them with acetone and ethanol in sequence, and vacuum dry them at 60℃ for 12h to obtain the core particles.

[0217] S4. Coat the core particles with a polyurethane microporous membrane to obtain core-shell type UV-resistant particles. The steps are the same as in Example 1.

[0218] Comparative Example 6

[0219] A UV-resistant, highly flame-retardant polyester fiber is prepared by means of the following components by weight: 100 parts polyester chips, 42 parts core particles, and 3 parts anti-drip agent; the anti-drip agent is triallyl isocyanurate. The preparation method of this polyester fiber includes the following steps:

[0220] 1) The polyester chips were vacuum dried at 110°C for 12 hours, and then mixed with the core particles and anti-drip agent at 600 rpm for 25 minutes to obtain the polyester mixture;

[0221] 2) The polyester blend is added to a twin-screw extruder and melt-extruded at 245°C. The resulting melt is spun to obtain UV-resistant and highly flame-retardant polyester fiber. The spinning temperature is 265°C, the spinning speed is 700 m / min, the draw ratio is 2, and the stretching rate is 700 m / min.

[0222] The preparation method of the core particles is the same as that in Example 1.

[0223] I. Performance Characterization

[0224] 1. Reference Figure 1 The infrared absorption spectra of the porous support (TiO2-Al2O3) and functionalized flame-retardant particles [TiO2-Al2O3@Mg(OH)2@Fe-CDs] prepared in Example 1 show that Mg(OH)2 and Fe-CDs were successfully loaded onto TiO2-Al2O3.

[0225] 2. Photothermal performance

[0226] 2-1. Add functionalized flame-retardant particles and deionized water to a container, and ultrasonically disperse for 20 min to prepare a dispersion with a concentration of 1.0 mg / mL. Irradiate the dispersion with a 350 nm ultraviolet light source for 10 min (the light source is located directly above the dispersion, 10 cm away), controlling the light source power density to be 1.0 W / cm³. 2 The ambient temperature was 25℃. An infrared thermal imager was used to record the temperature every 1 minute and plot a temperature-time curve.

[0227] Reference Figure 2 Temperature-time curves of the flame-retardant particles [TiO2-Al2O3@Mg(OH)2] and functionalized flame-retardant particles [TiO2-Al2O3@Mg(OH)2@Fe-CDs] prepared in Example 1 were used to test them. It can be seen that TiO2-Al2O3@Mg(OH)2@Fe-CDs exhibits significant photothermal properties, while TiO2-Al2O3@Mg(OH)2 does not. This comparison demonstrates that the photothermal properties originate from the modified carbon dots (Fe-CDs). Further testing showed that when continuously irradiated with ultraviolet light (12h), the temperature stabilized at approximately 84℃ and did not rise further. This is mainly due to limitations imposed by the light source power, the balance between heat generation and dissipation, and the photothermal efficiency of the functionalized flame-retardant particles. Therefore, the temperature induced by photothermal radiation has an upper limit and will not rise indefinitely. To further test the photothermal effect of adding core-shell flame-retardant and UV-resistant particles to polyester fibers, the polyester fibers prepared in Example 1 were tested using a 350nm UV light source (with the power density of the light source controlled at 1.0W / cm²). 2After continuous irradiation for 12 hours with a distance of 50 cm between the fiber and the polyester fiber, the highest local temperature in the polyester fiber was 89°C. Based on Example 1, the amount of core-shell flame-retardant and UV-resistant particles added was adjusted to 20 parts and 60 parts, and the highest temperatures obtained were 76°C and 97°C, respectively. This shows that after being added to the polyester fiber, the prepared polyester fiber also exhibited photothermal properties, and the temperature caused by photothermal activity also had an upper limit and would not rise indefinitely.

[0228] 2-2. The core-shell flame-retardant and UV-resistant particles from Examples 1-4 and Comparative Examples 2-3 were added to a container and prepared into a dispersion with a concentration of 1.0 mg / mL using deionized water. The dispersion was irradiated with a 350 nm UV light source for 10 min (the light source was positioned directly above the dispersion, 10 cm away), with the light source power density controlled at 1.0 W / cm². 2 The temperature of the system was detected using an infrared thermal imager. Following the guidelines in the literature "Lü Ju, Pan Lang, Qiu Yuheng, et al. Preparation, characterization and performance of photothermal and photodynamic synergistic antibacterial carbon dots [J]. Fine Chemicals, 2024, 41(8):1745-1753," the photothermal conversion efficiency η (%) was calculated using the following formula:

[0229] ;

[0230] In the formula: h is the heat transfer coefficient, with units of W / (m²). 2 ·K); S is the surface area of ​​the container, in m² 2 ;T m The highest steady-state temperature, in Kelvin (K); T r Ambient temperature (K); Q0 is the reference energy input for deionized water and container without added functionalized flame retardant particles (J); P is the power of the light source (W); A 350 The absorbance of the dispersion at 350 nm is given.

[0231] The photothermal conversion efficiency test results are shown in Table 1 below:

[0232] Table 1

[0233] Example 1 Example 2 Example 3 Example 4 Comparative Example 2 Comparative Example 3 Photo-thermal conversion efficiency η (%) 38.1 40.6 42.0 37.7 31.6 30.3

[0234] The results from Examples 1-3 show that the photothermal conversion efficiency of the core-shell flame-retardant and UV-resistant particles increases to some extent with the increase of the porogen content of polyethylene glycol, which is attributed to the increased porosity of the polyurethane microporous membrane due to the increased porogen content. The comparison between Comparative Examples 2-3 and Example 1 demonstrates that both Fe doping and the addition of indocyanine green in the photothermal agent (carbon dots) can improve the photothermal conversion efficiency.

[0235] 3. Ultraviolet absorption performance

[0236] ReferenceFigure 4 The UV-Vis absorption spectra of the core-shell flame-retardant and UV-resistant particles prepared in Example 1, Comparative Example 1, and Comparative Example 4 show that Example 1 has a wide UV absorption region, while the UV absorption capacity of Comparative Example 1 and Comparative Example 4 is significantly reduced, indicating that the photothermal agent and TiO2 in the core-shell flame-retardant and UV-resistant particles can improve the UV absorption performance.

[0237] 4. UV absorber release performance

[0238] Test method: Take 10g of the core-shell type flame-retardant and UV-resistant particles prepared in Example 1, wrap them in a filter bag, and place them in a glass container. Perform the following operations every 12 hours:

[0239] (1) Dark group (No Light): Add 50 mL of acetone and soak for 60 min, then rinse 3 times with acetone, take out, collect the rinsing liquid and soaking liquid, combine them, measure the total volume of the liquid, and use gas chromatography to detect the concentration of ultraviolet absorber UV-9 to obtain the release amount;

[0240] (2) Illumination group (350nm Light): Add 50mL of acetone and irradiate with 350nm light (the light source is located 20cm directly above the light source, and the power density is 1.0W / cm²). 2 Soak for 60 minutes, then rinse three times with acetone, remove, collect the rinsing liquid and soaking liquid, combine them, measure the total volume of the liquid, and use gas chromatography to detect the concentration of ultraviolet absorber UV-9 to obtain the release amount;

[0241] Two groups were tested continuously for 180 hours. Release curves were plotted with the accumulated release percentage (K) as the ordinate and the treatment time as the abscissa. Q t Q0 represents the cumulative release amount within time t, and Q0 represents the total load of UV-9 absorber. Q0 can be obtained by subtracting the mass of UV-9 absorber remaining in the impregnation solution of the additives after impregnation from the total mass of UV-9 absorber in acetone in step S4-1 of Example 1.

[0242] Test results are as follows Figure 5 As shown, both groups exhibited good sustained-release performance, and the release of UV-9, the ultraviolet absorber, increased significantly after increased light exposure. This indicates that the core-shell flame-retardant and UV-resistant particles can promote the release of the ultraviolet absorber under ultraviolet light, verifying their "adaptive regulation" performance.

[0243] II. Application Performance Testing

[0244] The polyester fibers prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to the following performance tests:

[0245] 1. UV protection properties

[0246] The ultraviolet transmittance was tested according to standard GB / T18830-2009, and the test results are shown in Table 2 below. Figure 6 , Figure 7 As shown:

[0247] Table 2

[0248] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 UVA transmittance / % 0.45 0.42 0.38 0.47 18.2 2.5 3.1 9.7 0.48 5.7 UVB transmittance / % 0.16 0.14 0.11 0.19 4.7 0.46 0.58 2.5 0.20 0.92

[0249] The test results show that Examples 1-4 exhibit excellent UV resistance. In Examples 2 and 3, the increased pore-forming agent content led to greater exposure of the UV-resistant active ingredients, resulting in enhanced UV resistance. In Comparative Example 1, the core-shell flame-retardant UV-resistant particles lacked modified carbon dots, resulting in a significant decrease in UV resistance. The results of Comparative Examples 2 and 3 indicate that Fe doping and the addition of indocyanine green to the carbon dots both improve UV resistance. In Comparative Example 4, the lack of TiO2 doping led to a substantial decrease in UV resistance. Comparative Example 5 showed no significant change in UV resistance. In Comparative Example 6, the absence of a polyurethane microporous membrane coating made it difficult for the core particles to disperse uniformly, affecting the performance of the active components and significantly reducing UV resistance.

[0250] 2. Flame retardant properties

[0251] The test was conducted according to standard GB / T 2406.2-2009, and the test results are shown in Table 3 below. Figure 8 As shown:

[0252] Table 3

[0253] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Limiting oxygen index (LOI) / % 39.4 38.7 38.2 39.1 38.2 39.1 39.3 38.6 30.3 30.9

[0254] 3. Fracture strength

[0255] The breaking strength of polyester fibers was measured according to the standard GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments". The test results are shown in Table 4 below. Figure 9 As shown:

[0256] Table 4

[0257] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Breaking strength (cN / detx) 3.52 3.41 3.30 3.49 3.50 3.54 3.52 2.91 3.23 3.12

[0258] The tensile strength after aging was tested: the polyester fiber was irradiated with 350nm ultraviolet light for 300h (distance between the light source and the sample 30cm, power 40W), and then the tensile strength was measured. The tensile strength retention rate was calculated as follows: tensile strength retention rate = (tensile strength after irradiation / tensile strength before irradiation) × 100%. The test results are shown in Table 5 below. Figure 10 As shown:

[0259] Table 5

[0260] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Breaking strength retention rate (%) 96.8 96.1 95.5 96.3 84.2 90.6 88.7 90.5 95.7 89.4

[0261] The test results show that Examples 1-4 have excellent UV aging resistance, while Comparative Examples 1-4 and Comparative Example 6 show varying degrees of decrease in UV aging resistance.

[0262] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.

Claims

1. An ultraviolet resistant high flame retardant polyester fiber, characterized by, The raw material for preparing the same comprises the following components in parts by weight: 100 parts of polyester chips, 20-60 parts of core-shell type flame-retardant anti-ultraviolet particles, 2-4.5 parts of anti-dripping agent; the core-shell type flame-retardant anti-ultraviolet particles are prepared by the following method: S1, preparing a porous carrier, the porous carrier being a composite of porous alumina and titanium dioxide; S2, loading magnesium hydroxide on the porous carrier to obtain flame-retardant particles; S3, modifying a photothermal agent on the flame-retardant particles to obtain functionalized flame-retardant particles, the photothermal agent being carbon dots with photothermal properties; S4, loading an auxiliary agent on the functionalized flame-retardant particles to obtain core particles, the auxiliary agent including an antioxidant and an ultraviolet absorber; S5, coating a polyurethane microporous membrane on the core particles to obtain core-shell type flame-retardant anti-ultraviolet particles.

2. The anti-UV high flame retardant polyester fiber according to claim 1, characterized by, The anti-dripping agent is at least one of melamine, phenyl melamine and triallyl isocyanurate; the antioxidant is at least one of antioxidant 1010, antioxidant 618, antioxidant 1076 and antioxidant 1098; and the ultraviolet absorber is at least one of UV-P, UV-1, UV-9, UVBP-4, UV-234 and UVP-327.

3. The anti-UV high flame retardant polyester fiber according to claim 1, characterized by, The core-shell type flame-retardant anti-ultraviolet particles are prepared by the following method: S1, preparing a porous carrier: using tetrabutyl titanate as a titanium source, AI(NO3)3·9H2O as an aluminum source, cetyltrimethylammonium bromide as a template agent and ammonium bicarbonate as a precipitating agent, a composite of porous alumina and titanium dioxide, i.e. a porous carrier, is prepared through hydrothermal reaction and calcination; S2, blending and reacting the porous carrier, MgCl2 and NaOH to load magnesium hydroxide on the porous carrier to obtain flame-retardant particles; S3, loading magnesium hydroxide: using glucose, ferric citrate, allyltrimethylammonium chloride, 4-dimethylaminopyridine and indocyanine green as raw materials, a mixture of ethanol and water as a solvent, carbon dots with photothermal properties are synthesized in situ on the flame-retardant particles through a hydrothermal method to obtain functionalized flame-retardant particles, the carbon dots being the photothermal agent; S4, loading an auxiliary agent: the auxiliary agent is loaded on the functionalized flame-retardant particles by a supergravity assisted impregnation method to obtain core particles, the auxiliary agent including an antioxidant and an ultraviolet absorber; S5, coating a polyurethane microporous membrane: the polyurethane microporous membrane is coated on the core particles to obtain core-shell type flame-retardant anti-ultraviolet particles.

4. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, Step S1 is specifically as follows: Tetrabutyl titanate is added into n-butanol to obtain liquid A, AI(NO3)3·9H2O and cetyltrimethylammonium bromide are taken into deionized water, ammonium bicarbonate is added, the obtained mixture is stirred and then added into a reaction kettle, the solid product is calcined at 400-550℃ for 2-8h after being reacted at 150-170℃ for 6-24h to obtain the porous carrier.

5. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, Step S2 is specifically as follows: the porous carrier is dispersed in deionized water, MgCl2 is added, NaOH aqueous solution is added dropwise, after dropwise addition is completed, the mixture is stirred and reacted at 40-60℃ for 1-4h, and then filtered, washed and dried to obtain the flame-retardant particles.

6. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, Step S3 is specifically as follows: S3-1, dispersing the flame-retardant particles and iron citrate in deionized water at a temperature of 60-80 DEG C to obtain a mixed solution 1; adding glucose, allyl trimethylammonium chloride, 4-dimethylamino pyridine and indocyanine green into a mixed solvent composed of ethanol and deionized water, and stirring to obtain a mixed solution 2; S3-2, adding the mixed solution 2 into the mixed solution 1, and transferring the obtained precursor solution into a reaction kettle, and reacting at 165-190 DEG C for 4-16 h, and then performing suction filtration, washing and drying to obtain the functionalized flame-retardant particles.

7. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, Step S4 is specifically: S4-1, adding the antioxidant and the ultraviolet absorber into acetone to prepare an auxiliary impregnation solution with an antioxidant concentration of 5-20 g / L and an ultraviolet absorber concentration of 3-12 g / L; S4-2, taking the functionalized flame-retardant particles into the impregnation solution, and performing ultrasonic dispersion for 0.5-2 h, and then placing in a supergravity packed bed, and treating under a supergravity condition of 25-100 times gravity acceleration for 2-8 h, and then taking out, and standing for 1-4 h, and then performing filtration, washing and drying to obtain the core particle.

8. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, Step S5 is specifically: S5-1, taking PPG, TDI and hydroxypropyl silicone oil into acetone, and heating to 55-75 DEG C, and then adding triethylene diamine dropwise, and stirring to react for 1-3 h, and then adding butanediol and ethylenediamine, and stirring to react at 70-75 DEG C for 1.5-6 h, and then removing acetone by reduced pressure distillation to obtain a modified polyurethane emulsion; S5-2, taking the modified polyurethane emulsion, the core particle and polyethylene glycol into a mixed solution composed of butanone and DMF, and stirring to react at 65-75 DEG C for 15-60 min, and then standing for 5-30 min, and then performing centrifugal separation, and then taking the obtained solid product into DMF, and stirring, and then performing suction filtration, and then taking the solid product into deionized water at a temperature of 70-80 DEG C, and stirring for 2-8 h, and then performing suction filtration and drying to obtain the core-shell type flame-retardant ultraviolet-resistant particle.

9. The anti-UV high flame retardant polyester fiber according to claim 3, characterized by, The core-shell type flame-retardant ultraviolet-resistant particle is prepared by the following method: S1, preparing a porous carrier: adding 0.85-3.4 mL tetrabutyl titanate into 25-100 mL n-butanol, and stirring for 2-10 min to obtain A liquid; taking 5-20 g AI(NO3)3·9H2O and 0.12-0.5 g cetyltrimethylammonium bromide into 75-300 mL deionized water, and stirring for 5-20 min, and then adding 4-16 g ammonium bicarbonate, and stirring for 15-60 min, and then adding the A liquid, and ultrasonic dispersing for 0.5-2 h, and then taking the obtained mixture into a reaction kettle, and reacting at 150-170 DEG C for 6-24 h, and then cooling to room temperature, and then performing suction filtration, washing and drying, and then calcining at 650-750 DEG C for 2-8 h, and then grinding to obtain the porous carrier; S2, loading magnesium hydroxide on the porous carrier: taking 2.5-10 g of the porous carrier and dispersing in 100-400 mL deionized water, and adding 1.5-6.3 g MgCl2, and adding 30-150 mL 1 mol / L NaOH aqueous solution dropwise under stirring, and stirring to react at 40-60 DEG C for 1-4 h, and then performing filtration, washing and drying to obtain the flame-retardant particle; S3, modifying the photothermal agent on the flame-retardant particle: S3-1, dispersing 2.5-10 g flame-retardant particles and 612-2450 mg iron citrate in 50-200 mL deionized water at 60-80℃ to obtain a mixed solution 1; adding 450-1800 mg glucose, 200-814 mg allyltrimethylammonium chloride, 122-488 mg 4-dimethylaminopyridine and 220-930 mg indocyanine green into a mixed solvent composed of 20-80 mL ethanol and 30-120 mL deionized water, stirring for 5-30 min to obtain a mixed solution 2; S3-2, adding the mixed solution 2 into the mixed solution 1 under stirring, ultrasonic dispersion at 60-80℃ for 5-20 min, transferring the obtained precursor solution into a reaction kettle, reaction at 165-190℃ for 4-16 h, cooling, suction filtration, washing and drying to obtain functionalized flame-retardant particles; S4, loading auxiliary agents on the functionalized flame-retardant particles: S4-1, adding antioxidants and ultraviolet absorbers into acetone, stirring uniformly to prepare an auxiliary agent impregnation solution with an antioxidant concentration of 5-20 g / L and an ultraviolet absorber concentration of 3-12 g / L; S4-2, taking 2.5-10 g functionalized flame-retardant particles into 50-200 mL impregnation solution, ultrasonic dispersion for 0.5-2 h, then placing in a high gravity packed bed, treating under a high gravity condition of 100-400 times gravity acceleration for 2-8 h, then taking out, standing for 1-4 h, filtering, washing and drying to obtain core particles; S5, coating polyurethane microporous membrane on the core particles: S5-1, taking 2.5-10 g PPG, 1.75-7 g TDI and 0.7-2.8 g hydroxypropyl silicone oil into 50-200 mL acetone, heating to 55-75℃ under nitrogen protection, then adding 0.005-0.03 g triethylenediamine dropwise, stirring for 1-3 h, adding 1-4 mL butanediol and 0.4-1.6 mL ethylenediamine, stirring at 70-75℃ for 1.5-6 h, reducing to room temperature, removing acetone by reduced pressure distillation to obtain a modified polyurethane emulsion; S5-2, taking 2.5-10 g modified polyurethane emulsion, 1.25-5 g core particles and 0.28-1.12 g polyethylene glycol into a mixed solution composed of 15-60 mL butanone and 15-60 mL DMF, stirring for 5-30 min, stirring at 65-75℃ for 15-60 min, standing for 5-30 min, reducing to room temperature and centrifuging, then adding the obtained solid product into 25-100 mL DMF, stirring for 5-20 min, suction filtering, adding the solid product into 50-200 mL deionized water at 70-80℃, stirring for 2-8 h, suction filtering and drying to obtain core-shell type flame-retardant ultraviolet-resistant particles.

10. A method for preparing the anti-UV high flame-retardant polyester fiber according to any one of claims 1 to 9, characterized by, including the following steps: 1) vacuum drying polyester chips at 100-120℃ for 6-24 h, then stirring and mixing with the core-shell type flame-retardant ultraviolet-resistant particles and anti-dripping agent to obtain a polyester mixture; 2) melt-extruding the polyester mixture at 230-245 DEG C, spinning the obtained melt to obtain the ultraviolet resistant high flame-retardant polyester fiber, the spinning temperature being 250-270 DEG C and the spinning speed being 600-900 m / min.

Citation Information

Patent Citations

  • Flexible polyester fiber packing belt and preparation method thereof

    CN105802146A

  • Warm-keeping moisture-conducting multifunctional polyester fiber and preparation method thereof

    CN111979585A

  • Extinction PET fiber chip spinning preparation process

    CN119956520A

  • Antibacterial elastic polyester fiber and preparation method thereof

    CN120041963A

  • Slow-release antioxidant as well as preparation method and application thereof

    CN120098689A

Cited By

  • Preparation method of high-performance anti-ultraviolet water-repellent polyester fiber

    CN122039429A

  • Preparation method of high-performance uvioresistant water-repellent polyester fiber

    CN122039429B